Massive Acute Spinal Subdural Hematoma Causing Sudden Onset Paraplegia in a Patient on Anticoagulation. (16th November 2020) - Kosarchuk, Jacob; Lewis, Courtney; Pham, Martin H.
Abstract : Spinal subdural hematoma (SSDH) is a rare but known entity that can cause severe and irreversible motor, sensory, and autonomic dysfunction if not decompressed in a timely manner. We present here a 74-year-old female on anticoagulation who developed sudden onset back pain with rapidly progressive paraplegia. On neurologic exam, she was completely flaccid in the bilateral lower extremities with absent sensation from the umbilicus down. Imaging demonstrated a massive extra-axial spinal hematoma from T12 to S1 that initially was believed to be epidural in origin. She was taken emergently to the operating room for a T11-L5 decompressive laminectomy, and dural opening demonstrated a thick subdural clot encasing the conus and cauda equina confirming the subdural pathology. Despite decompression and partial evacuation of the subdural hematoma, she did not recover neurologic function.